MAB에 의한 생물학적 질산화와 탈질산화 개선 - 강용태; 장영일; 김태기; 한상윤; 손정호; 김연은 (한국수처리학회지, 18(6), 2010)
This study was conducted the effect of MAB in activated sludge to research about nitrification and denitrification. Membrane module settled in aerobic bioreactor. And pure-oxygen was supplied to inner membrane heating & cooling system which were used for control of pure oxygen temperature. As a result, nitrification, denitrification and organic carbon removal were simultaneously fulfilled by MAB which was applied to activated sludge in bioreactor. In MAB, nitrification rate changes reacted sensitively by temperature changes of supplied pure-oxygen. About 35℃ of pure-oxygen could make optimal environment of biofilm attachment & growth even low water temperature. Thus, improvement of nitrification rate, denitrification, microorganism number and decrease of excess sludge were very effective in general field of wastewater treatment in case MAB was applied. KCI Citation Count: 1